Production of Biocomposite from Parinari Polyandra Fruit Shell Using Waste Low Density Polyethylene as Matrix - Odiase, P. O.; Odetoye, T. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Enormous wastes that are continuously being generated from low-density polyethylene (LDPE) film sachet water have remained an environmental challenge in Nigeria. These might require urgent action due to the non-biodegradability of LDPE.  Biocomposite samples were produced using waste LDPE sachets and Parinari polyandra shells, where filler sizes (0.420 mm, 0.841mm) and filler loading (10%, 20%) were varied. In this study, a melt mixer was designed and fabricated for the production of bio composite samples. Biocomposite samples were characterized using tensile tests, compression test, flexural and impact strength test, water absorption test, biodegradability, fourier transform infrared spectroscopy and scanning electron microscopy tests. Viscosity of the bio composite mix was a major constrain in the design of the melt mixer. The results revealed that the optimum value of tensile strength was obtained with particle size 0.42mm at a 10% filler to matrix loading which produced a Young’s modulus of 320.321 N/mm2. Higher particle size and filler loading elicited a higher value for compressive strength based on a force at peak value of 27552.500 N. Flexural, impact and tensile strength decreased with increasing filler loading and particle size, while increased immersion time gave increased percentage of water absorbed.